Legal Protection for Workers' Rights Due to Termination of Employment in Tangerang Regency - Maksum, Maksum (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
This study aims to analyze the legal protection provided to workers affected by termination of employment (PHK) in Tangerang Regency. The research utilizes an empirical juridical method, which involves examining the application or implementation of normative legal provisions in real-life legal events occurring in society. The legal protection for workers affected by termination of employment is clearly stipulated in the Indonesian Law No. 6 of 2023 concerning the enactment of Government Regulation in Lieu of Law No. 2 of 2022 on Job Creation, specifically in Chapter IV, Articles 150 to 160. Article 156, That employers are required to provide severance pay, service compensation, and compensation for rights that workers are entitled to receive if their employment is terminated. Several factors influencing legal protection for workers' rights following termination in Tangerang Regency include: the existence of many practices that deviate from labor regulations, often exploited by employers to avoid paying workers' entitlements; lack of knowledge and awareness from both employers and workers regarding their rights and obligations; cultural factors from both workers, employers, and law enforcers; despite the theoretical balance between employers and employees, the practical reality often differs; and the financial capability of companies to meet workers' rights. Proposed solutions include: verification of every employment contract, company regulation, and collective labor agreements in companies operating in Tangerang Regency; fostering better understanding and collaboration between employers and workers (labor unions) as a preventive measure against violations of workers' rights and industrial disputes; regular dissemination of labor regulations to enhance employers’ and workers' awareness; government intervention through more adequate regulations, along with strengthened guidance, supervision, and law enforcement.